2015
DOI: 10.33549/physiolres.932834
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Nrf2 by Ischemic Preconditioning and Sulforaphane in Renal Ischemia/Reperfusion Injury: a Comparative Experimental Study

Abstract: Objectives of the study were to investigate impact of ischemic preconditioning (Ipre) and sulforaphane (SFN) and combination of them on nuclear factor 2 erythroid related factor 2 (Nrf2) gene and its dependent genes, heme oxygenase-1 (HO1) and NADPH-quinone oxidoreductase1 (NQO-1) and inflammatory cytokines TNF-α, IL1β, and intercellular adhesion molecule-1 (ICAM1) and caspase-3 in renal ischemia/reperfusion (I/R) injury. Ninety male Sprague Dawely rats were classified into 5 groups (each consists of 18 rats):… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 31 publications
0
31
1
1
Order By: Relevance
“…In consistent with our study, administration of EPO along with sodium selenite decreased oxidative stress and activated PI3K/NO signaling pathway (Liu et al 2015) in a rat ischemia-reperfusion induced renal injury model. Shokeir et al (2015) documented that combination of IPC and sulforaphone offered more improvements in the antioxidant enzymes and inflammatory state, but not the apoptotic markers.…”
Section: Discussionmentioning
confidence: 99%
“…In consistent with our study, administration of EPO along with sodium selenite decreased oxidative stress and activated PI3K/NO signaling pathway (Liu et al 2015) in a rat ischemia-reperfusion induced renal injury model. Shokeir et al (2015) documented that combination of IPC and sulforaphone offered more improvements in the antioxidant enzymes and inflammatory state, but not the apoptotic markers.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS), apoptosis, cytokines, chemokines, and leukocytes activation play an important role in its underlying mechanisms (Jang and Rabb, 2009;Sharfuddin and Molitoris, 2011), therefore, it is imperative to find effective therapies and elucidate molecular mechanisms by which renal I/R injury may be attenuated. Antioxidants such as sulforaphane, oxymatrine and gelsemine have been demonstrated to protect murine kidneys against I/R injury (Shokeir et al, 2015;Jiang et al, 2015;Lin et al, 2015). These findings indicated that renal I/R injury might be ameliorated via targeting oxidative stress.…”
Section: Discussionmentioning
confidence: 92%
“…Selenium upregulated antioxidants in a pig model of transplanted kidneys (ischemia-reperfusion injury) 88 . Sulforaphane, a natural dietary isothiocyanate, has been shown to be renoprotective and able to improve kidney function in an animal renal IRI model 89 . In this study, Shokeir et al showed that ischemic preconditioning and sulforaphane both enhanced gene expression (Nrf2, heme oxygenase-1 HO-1, NADPH-quinone oxidoreductase1 NQO-1) and diminished the inflammatory (TNF-α, IL-1, ICAM-1) and apoptotic markers (caspase-3), with better results for sulforaphane alone.…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%